Mechanisms of Therapy Resistance in Patient-Derived Xenograft Models of BRCA1-Deficient Breast Cancer - Ter Brugge, Petra; Kristel, Petra; van der Burg, Eline; Boon, Ute; de Maaker, Michiel; Lips, Esther; Mulder, Lennart; de Ruiter, Julian; Moutinho, Catia; Gevensleben, Heidrun; Marangoni, Elisabetta; Majewski, Ian; et al. (JNCI : Journal of the National Cancer Institute, 2016)
Although BRCA1-deficient tumors are extremely sensitive to DNA-damaging drugs and poly(ADP-ribose) polymerase (PARP) inhibitors, recurrences do occur and, consequently, resistance to therapy remains a serious clinical problem. To study the underlying mechanisms, we induced therapy resistance in patient-derived xenograft (PDX) models of BRCA1-mutated and BRCA1-methylated triple-negative breast cancer. A cohort of 75 mice carrying BRCA1-deficient breast PDX tumors was treated with cisplatin, melphalan, nimustine, or olaparib, and treatment sensitivity was determined. In tumors that acquired therapy resistance, BRCA1 expression was investigated using quantitative real-time polymerase chain reaction and immunoblotting. Next-generation sequencing, methylation-specific multiplex ligation-dependent probe amplification (MLPA) and Target Locus Amplification (TLA)-based sequencing were used to determine mechanisms of BRCA1 re-expression in therapy-resistant tumors. BRCA1 protein was not detected in therapy-sensitive tumors but was found in 31 out of 42 resistant cases. Apart from previously described mechanisms involving BRCA1-intragenic deletions and loss of BRCA1 promoter hypermethylation, a novel resistance mechanism was identified in four out of seven BRCA1-methylated PDX tumors that re-expressed BRCA1 but retained BRCA1 promoter hypermethylation. In these tumors, we found de novo gene fusions that placed BRCA1 under the transcriptional control of a heterologous promoter, resulting in re-expression of BRCA1 and acquisition of therapy resistance. In addition to previously described clinically relevant resistance mechanisms in BRCA1-deficient tumors, we describe a novel resistance mechanism in BRCA1-methylated PDX tumors involving de novo rearrangements at the BRCA1 locus, demonstrating that BRCA1-methylated breast cancers may acquire therapy resistance via both epigenetic and genetic mechanisms.